PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PELANGGA PT INDONESIA STANLEY ELECTRIC DI KABUPATEN TANGERANG - Ananda Puspita; Putri Nilam Kencana (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of Product Promotion and Quality on Purchase Decisions on PT Indonesia Stanley Electric Customers in Tangerang Regency both partially and simultaneously. The method used is the quantitative method. Data collection technique using cosioner, the population is 733 consumers, sampling can use the slovin formula, then the sample is all consumers totaling 88 consumers. Data analysis techniques use validity tests, reliability tests, classical assumptions tests, regression analysis, determination coefficient analysis and hypothesis tests. The result of this study is that Promotion has a significant effect on the Purchase Decision with the regression equation Y = 17,994 + 0.562X1. With a correlation coefficient of 0.660, the two variables have a strong relationship. The determination coefficient value of 0.436 means that the purchase decision is affected by the promotion of 43.6% and the hypothesis test is obtained by the value of t count > t table or (8,151 > 1,988) then H0 is rejected and H1 is accepted. Product quality has a significant effect on the Purchase Decision with the regression equation Y = 11.484 + 0.719X2. With a correlation coefficient of 0.720, the two variables have a strong relationship. The determination coefficient value of 0.519 means that the purchase decision is influenced by the product quality of 51.9% and the hypothesis test is obtained by a value of (9.624 > 1.988) then H0 is rejected and H2 is accepted. Promotion and product quality have a significant effect on purchasing decisions with regression equation Y= 9,368 + 0.280X1 + 0.503X2. With a correlation coefficient value of 0.720, promotion and product quality have a strong relationship with the purchase decision, with a determination coefficient value of 0.580, meaning that the purchase decision is influenced by promotion and product quality of 58%. The hypothesis test obtained a value of F count > F table or (58,733 > 3,10). Thus Ho was rejected and H3 was accepted.